A fast micro–nano liquid layer induced construction of scaled-up oxyhydroxide based electrocatalysts for alkaline water splitting. Issue 47 (23rd November 2021) - Yan, Yaotian; Liu, Juqing; Huang, Keke; Qi, Junlei; Qiao, Liang; Zheng, Xiaohang; Cai, Wei
Abstract : A fast micro–nano liquid layer induced construction of self-supported electrocatalysts is proposed at room temperature. The as-synthesized Fe based oxyhydroxide exhibits an excellent cost-efficiency ratio for overall water-splitting. Abstract : Electrocatalysis is vital for the development of the future hydrogen economy, highlighting the critical significance of the macro-preparation of nanostructured electrocatalysts. Herein, a fast micro–nano liquid layer induced construction (MLC) strategy is proposed, ensuring a tenfold increase in electrode size with almost negligible heat consumption. As a conceptual application model, cation coupled FeOOH nanosheets of thousands of square centimetres are synthesized within 20 minutes at room temperature for water splitting. Density functional theory (DFT) calculations further reveal that the modulation of binary cations (Ni and Zr) leads to charge accumulation around Fe sites. This results in a more balanced proton adsorption for the HER, as well as a lowered energy barrier for the OER. The proposed strategy paves the way for the scaled-up synthesis of nanostructured electrocatalysts, and also provides a platform for exploring more functional nanostructured compounds.